Development of ready-to-drink (RTD) sweet potato (Ipomea batatas) leaf extract (SPLE) with black tea in doy packs - Pestio, Justin Emil P.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The study aimed to develop a ready-to-drink sweet potato leaf extract with black tea in doy packs. Different maturities (1.5 mo and 3 mo) and varieties (Inubi and Kinerots) were considered for the study. Models were generated in order to predict the effects of level of calamansi-honey concentrate (CHC) (mL/100 mL sweet potato leaf extract (SPLE)), amount of black tea (BT) (g/100 mL SPLE) and processing time (PT) (min) on the pH and overall acceptability of the juice drink using response surface methodology (RSM). Results show that calamansi-honey concentrate had a significant (p<0.05) effect on the pH while both black tea and calamansi-honey concentrate had linear effects (p<0.05) on the overall acceptability. Results show that the optimal combinations of: (1) Young Inubi (CHC: 9.58-9.84 mL/100 mL SPLE, BT: 2.00 g/ 100 mL SPLE, PT: 2.00-2.13 min); (2) Young Kinerots (CHC: 10.15-11.46 mL/100 mL SPLE, BT: 1.98-2.00 g/100 mL SPLE, PT: 2.00-2.15 min); (3) Mature Inubi (CHC: 10.62-11.10 mL/100 mL SPLE, PT: 2.00-2.13 min); (4) Mature Kinerots (CHC: 11.45-11.59 mL/ 100 mL SPLE, BT: 1.96-2.00 g/100 mL SPLE, PT: 2.00-2.12 min) are capable of producing a beverage with a desirable range of pH and overall acceptability. Verification runs were able to validate the predictive capacity and accuracy of the statistical models in predicting responses. This study showed the potential of sweet potato leaves in the production of a ready-to-drink (RTD) beverage.
submitted June 2017
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Sweet potato leaves; Vegetable juices